The Crisis $1 (BVolume 06s - Churchill, Winston, 1871-1947 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Crisis $1 (BVolume 06" by Winston Churchill is a historical novel published in 1901. Set in St. Louis during the turbulent years before the Civil War, it follows young Stephen Brice, a Union supporter from Boston, as he becomes entangled with a Southern family. Romantic rivalries unfold between four central characters against the backdrop of a divided Missouri. Abraham Lincoln emerges as a powerful moral presence, his opposition to slavery's extension igniting the crisis that will transform lives and test loyalties in a nation heading toward war. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Crisis_(novel)
Release date is 2004-10-19
Produced by David Widger
Keywords: United States -- History -- Civil War, 1861-1865 -- Fiction